2011
DOI: 10.1177/183693911103600204
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Symbolic Play and Executive Function in Young Children

Abstract: THE ROlE Of ExECuTIVE fuNCTION, specifically inhibitory control and generativity, in symbolic play was investigated in 20 children aged 48-89 months. Assessment of inhibitory control was via the Sun-Moon Stroop task, and generativity was assessed with the Semantic Fluency task, as well as a new object substitution task which required children to generate as many uses of toys as possible. Symbolic play ability was assessed under both structured conditions, using the Test of Pretend Play (Lewis & Boucher, 1997),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
4
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(43 citation statements)
references
References 44 publications
5
30
4
4
Order By: Relevance
“…The results revealed there is indeed a robust, positive correlation between EF and the ability to manage dual representations in pretense. These findings held for relatively cool conflict measures of EF, as suggested by previous smaller studies (Albertson & Shore, 2009; Kelly & Hammond, 2011), but there was also new evidence for a relation between pretend actions and performance on relatively hot, delay-of-gratification measures. The results were reciprocal when we examined both EF—Pretense and Pretense EF—regressions.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results revealed there is indeed a robust, positive correlation between EF and the ability to manage dual representations in pretense. These findings held for relatively cool conflict measures of EF, as suggested by previous smaller studies (Albertson & Shore, 2009; Kelly & Hammond, 2011), but there was also new evidence for a relation between pretend actions and performance on relatively hot, delay-of-gratification measures. The results were reciprocal when we examined both EF—Pretense and Pretense EF—regressions.…”
Section: Discussionsupporting
confidence: 80%
“…Children’s ability to later recall both the real and pretend identities of an object significantly correlated with scores on a set of three conflict EF tasks. Finally, after controlling for mental age, Kelly and Hammond (2011) found a relation between structured pretend play and a version of the Day/Night inhibitory control task among preschoolers. Although these studies reveal a link between pretense and self-regulation, they were limited by several factors, such as small sample sizes for correlational analyses and few behavioral measures of EF and control variables.…”
Section: Introductionmentioning
confidence: 85%
“…Three other studies found a relationship to laboratory tests of knowledge about pretend play (Albertson & Shore, 2009;Carlson, White, & Davis-Unger, 2012;Kelly, Hammond, Dissanayake, & Ihsen, 2011); however, the knowledge tests themselves appear to require EF. What would be most telling is if engaging in pretend play were itself related to EF.…”
Section: Executive Functionmentioning
confidence: 89%
“…Moreover, although the studies reviewed above provide suggestive evidence on the relations between the complexity of pretend play and displayed cognitive and emotional self‐regulation behavior, none of the studies included measures of children's cool and hot executive functions as control variables. Therefore, the previously observed relationships may, at least partly, be caused by involvement of executive functions in both play behavior (Carlson et al, ; Kelly & Hammond, ) and self‐regulation (e.g., Bryce et al, ; Denham, Warren‐Khot, et al, ). In this study, relations between complexity of pretend play and both cognitive and emotional self‐regulation are investigated, while controlling for children's cool and hot executive functions.…”
Section: Introductionmentioning
confidence: 97%